Caesarism in the Post-Revolutionary Age Crisis, Populace and Leadership - Prutsch, Markus J. (Bloomsbury Academic, 2020)
Debates about the legitimacy and 'essence' of political rule and the search for 'ideal' forms of government have been at the very heart of political thought ever since its beginnings in the Ancient World. Caesarism in the Post-Revolutionary Age explores the complex relationship between democracy and dictatorship from the 18th century onwards. More concretely, it assesses how, during the post-revolutionary period, democracy emerged as something compatible with dictatorship, both on the level of political thought and practice.